Jogo de tabuleiro: estratégia educativa sobre o uso de álcool em adolescentes - Caliari, Tamires Marta (2018)
Adolescents' alcohol consumption begins earlier because of various social, cultural, school, family and because of the influence of friends. The abusive use of alcohol causes alterations in reasoning, motor coordination, causes physical, psychic and social impairment. Therefore, there is a need for strategies in schools, in families and in society with the aim of educating on this theme. The objectives of this research were develop a board game as an educational strategy on the use of alcoholic drinks in adolescents and analyze the perception of these adolescents on this subject before and after the application of the board game. It is a study with active methodology in the construction and refinement of the game of board and qualitative for the analysis of the adolescents' perception about the use of alcoholic beverages. The study sample consisted of adolescents from the sixth year of primary education in the age group of 10 to 13 years of a public school in the South of Minas Gerais, Brazil. The assembly of the game from the playful creation, game board illustration and cards were created by the researcher with the collaboration of a designer and a graphic designer, materializing the final version of the game "You Decide". After construction, the board game had the evaluation of the judges, thus the game was updated with the observations of these judges and structured in its final version, applying to the adolescents subjects of the study. Data collection took place in focal group with 6 to 12 adolescents. Data records were recorded by recording, observations and field journal annotations. The collected data were analyzed referring to the Bardin Content Analysis: pre-analysis, material exploration and treatment of results, inference and interpretation. After the application of the board game "You Decide", five focus groups were formed with 46 adolescents, forming of this process, with the testimonies of adolescents, two categories and two subcategories. The first category refers to "Scientific background and legislation: adolescent empowerment" and the second to "The use of alcoholic beverages in adolescence and its interfaces: family, social behavior and health", encompassing two subcategories: "Domestic violence : from aggression to death "and" Use of alcoholic beverages: influence on behavior and health ". The "You Decide" game, as an educational tool, made it possible for teenagers to become aware of the use of alcoholic beverages, which was previously seen as something natural, pleasant, permissive and present in the family, now seen as something forbidden and causing evils in their lives. There is also an awareness of the abusive acts suffered and witnessed, now identified as acts of violence that should not be tolerated and natural in their daily lives. The game also provided adolescents with a moral conscience in the face of carelessness in traffic, due to the use of alcoholic beverages, and a knowledge and awareness of the maladies and morbidities caused in the body by the alcoholic beverage, which can cause death. The game "You Decide" presents itself as an educational strategy to promote adolescents' health and practice in nursing. The playful tool interactive and pleasurable made it possible innovate health education. favored the development of autonomy and empowerment, which could result in greater awareness, autonomy and decision-making in the face of common challenges to the process of becoming a teenager.